"Left behind": why implementing migration-aware responses to HIV for migrant farm workers is a priority for South Africa. Issue 1 (2nd January 2020) - Gruchy, Thea de; Vearey, Jo
Abstract : Like many other countries, South Africa (SA) has committed to the Sustainable Development Goals that aim to "leave no-one behind", in efforts towards universal health coverage, and meeting the UNAIDS 90–90–90 targets through the implementation of universal test and treat (UTT) interventions. SA is associated with high levels of international and internal migration that, in certain contexts, are known to (1) increase the risk of acquiring HIV and (2) present challenges to HIV treatment access and continuity. Despite this, migration and mobility are not adequately considered in responses to HIV. As SA rolls out UTT programmes and antiretroviral treatment as prevention (TasP) interventions, including pre-exposure prophylaxis (PreP), there is an urgent need to ensure that these are migration-aware and mobility-competent. In SA, a key population that experiences a disproportionate HIV burden is international migrant farm workers living and working on commercial farms along the border with Zimbabwe. In this article, a social determinants of health approach is applied to explore the context within which this population struggles to access positive determinants of health, including the public health care system, and the implications of this for HIV programming. It is argued that, unless policies and programming become migration-aware and mobility-competent, UTT and TasP interventions will struggle to address the high burden of HIV among this population and, as a result, progress towards global health targets will be limited.